ANALISIS PEMAHAMAN SISWA BERDASARKAN TEORI APOS MATERI BALOK DAN KUBUS DITINJAU DARI KECERDASAN EMOSIONAL - Saputri, Adhila Nuril; Sunardi, S; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2018)
Abstract. This research aims to describe students’ comprehension based on apos theory on the theme “cuboid and cube” from the perspective of emotional quotient of grade IX A students SMP Negeri 1 Semboro. This research is a descriptive study with qualitative approach. APOS theory assumes that understand of mathematical concept is a result of construction or reconstruction of mathematical object. Construction or reconstruction is done by action, processes, and object that are coordination in a scheme to solve the problems. So, we can know comprehension student of mathematical concept can use APOS theory. Subjects of this study were 6 students consist of 2 students with high emotional quotient, 2 students with moderate emotional quotient and 2 students with low emotional quotient. Data collection obtained with emotional quotient questionnaires, test, and interview. Based on the results of the analysis, the results can be obtained that students with high emotional quotient has reached the stage of action, process, object, and scheme; the comprehension of students with moderate emotional quotient has reached the stage of action, process, and object; the comprehension of students with low emotional quotient just has reached the stage of action, has not reached the process, object, and scheme. Keywords: Comprehension, APOS theory, Emotional quotient, Cuboid and Cube.